Compound heterozygosity for TNXB genetic variants in a mixed‐breed dog with Ehlers‐Danlos syndrome. (31st July 2019) - Bauer, A.; de Lucia, M.; Leuthard, F.; Jagannathan, V.; Leeb, T.
Summary: The Ehlers‐Danlos syndromes (EDSs) are a heterogeneous group of inherited connective tissue disorders characterized by skin hyperextensibility, joint hypermobility and tissue fragility. Inherited disorders similar to human EDS have been reported in different mammalian species. In the present study, we investigated a female mixed‐breed dog with clinical signs of EDS. Whole‐genome sequencing of the affected dog revealed two missense variants in the TNXB gene, encoding the extracellular matrix protein tenascin XB. In humans, TNXB genetic variants cause classical‐like EDS or the milder hypermobile EDS. The affected dog was heterozygous at both identified variants. Each variant allele was transmitted from one of the case's parents, consistent with compound heterozygosity. Although one of the variant alleles, XM_003431680.3:c.2012G>A, p.(Ser671Asn), was private to the family of the affected dog and absent from whole‐genome sequencing data of 599 control dogs, the second variant allele, XM_003431680.3:c.2900G>A, p.(Gly967Asp), is present at a low frequency in the Chihuahua and Poodle population. Given that TNXB is a functional candidate gene for EDS, we suggest that compound heterozygosity for the identified TNXB variants may have caused the EDS‐like phenotype in the affected dog. Chihuahuas and Poodles should be monitored for EDS cases, which might confirm the hypothesized pathogenic effect of the segregating TNXB variant.